Skeleton vol. 5 [videorecording]. - Dorling Kindersley Vision; Sachs, Andrew narrator; Lionheart Television (London Dorling Kindersley Ltd., 1994)
Skeleton delves beneath the surface to reveal the hidden secrets of our invaluable support systems, and symbol of our deepest fear. Most animals have skeletons. We explore how these have developed into an incredible variety of structures, none more complex than our own human skeleton.
Eyewitness presents the ultimate natural history experience. The series takes the viewer on a dazzling wildlife tour, interweaving fact, history, anecdote, myth and legend with energy and homour. Fast-paced and full of stunning graphics, Eyewitness is an enriching experience for all ages.
Director: David Hutt. Graphic Director: Alisa Robbins. Writer: David Hanson. Music: Guy Michelmore. Executive Producer: Simon Jollands and Eve Krzyzanowski. Series Producer: Bill Butt
Keywords: Skeleton